Small RNAs: Analysis and Regulatory Functions - Nellen, Wolfgang; Hammann, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
In recent years Molecular Biology has experienced an unprecedented revolution by the discovery of functional small RNAs. The number of cellular processes in which non-coding RNAs are involved is growing rapidly and include gene regulation on the transcriptional, post-transcriptional and translational level. To complicate matters, these processes seem to be strongly interconnected on the one hand, and diverse among different organisms on the other. This volume describes strategies for the discovery and validation of small RNAs and provides a snapshot of our current understanding of the different mechanisms triggered by small RNAs.
Small Regulatory RNAs in Bacteria -- Small Nucleolar RNAs: Identification, Structure, and Function -- A Computational Approach to Search for Non-Coding RNAs in Large Genomic Data -- Experimental Strategies for the Identification and Validation of Target RNAs that Are Regulated by miRNAs -- Protein Interactions with Double-Stranded RNA in Eukaryotic Cells -- Transitive and Systemic RNA Silencing: Both Involving an RNA Amplification Mechanism? -- RNA Interference and Antisense Mediated Gene Silencing -- Epigenetic Silencing of Transposons in the Green Alga Chlamydomonas reinhardtii -- RNA-Dependent Gene Silencing and Epigenetics in Animals -- Potentials of a Ribozyme-Based Gene Discovery System.
Keywords: Biochemistry; Cell biology; Developmental biology; Biochemistry, general; Cell Biology; Developmental Biology